2001
DOI: 10.1046/j.0306-5251.2001.01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Human thiopurine methyltransferase activity varies with red blood cell age

Abstract: Aims  Inherited differences in thiopurine methyltransferase (TPMT) activity are an important factor in the wide interindividual variations observed in the clinical response to thiopurine chemotherapy. The aim of this study was to establish a population range for red blood cell (RBC) TPMT activity in children with acute lymphoblastic leukaemia (ALL) at disease diagnosis. An additional aim was to investigate factors that can influence TPMT activity within the RBC. Methods  Blood samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 26 publications
3
45
0
1
Order By: Relevance
“…Even though not specifically investigated in our study, the RBCs do not constitute a homogenous group and the RBCs have a life span of 120 days. Lennard et al (2001) showed that the RBC population at diagnosis was influenced by the disturbed haematopoiesis and the population consisted of an excess of old RBCs [14]. In that study, a density gradient centrifugation of the red blood cells showed that the population corresponding to the older cells displayed a lower TPMT enzyme activity compared to newer cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Even though not specifically investigated in our study, the RBCs do not constitute a homogenous group and the RBCs have a life span of 120 days. Lennard et al (2001) showed that the RBC population at diagnosis was influenced by the disturbed haematopoiesis and the population consisted of an excess of old RBCs [14]. In that study, a density gradient centrifugation of the red blood cells showed that the population corresponding to the older cells displayed a lower TPMT enzyme activity compared to newer cells.…”
Section: Discussionmentioning
confidence: 88%
“…The TPMT enzyme activity in MOLT4 cells was determined by measuring the rate of formation of 6-methyl-mercaptopurine from 6-MP using 14 C-labeled S-adenosyl-Lmethionine as the methyl group donor [12]. An amount of 200 µg of the total cellular protein was incubated in duplicates for 2 hours at 37°C in 400 µl of 47 mmol/l potassium phosphate buffer (pH 7.…”
Section: Tpmt Enzyme Activity In Molt4 Cellsmentioning
confidence: 99%
“…18 TPMT phenotype has been assigned on the basis of its activity in erythrocytes as previously described, 19 but these measurements are laborious and vary with red blood cell age. 20 Furthermore, bimodal or trimodal activity patterns have been shown in several populations. 16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] Since ethnic differences have been demonstrated worldwide, it remains to be elucidated in Brazil, the fifth largest populated country in the world.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although TPMT deficiency can be diagnosed by assays of erythrocyte TPMT activity, different factors, including patient age, renal function, receiving of RBC transfusion and thiopurine administration, may alter these results. 15,16,21 Molecular genetic (PCR-based) methods are not affected by extraneous factors and offer a promising alternative to measurement of RBC TPMT activity. PCR-based methods require less than 1 mg of DNA, which is the amount contained in approximately 100 ml of whole blood.…”
Section: Discussionmentioning
confidence: 99%